Fatal bovine anaplasmosis in a herd with new genotypes of Anaplasma marginale, Anaplasma ovis and concurrent haemoplasmosis - Hornok, S. (2012)
Haematological and molecular analysis of blood samples was carried out during an outbreak of bovine anaplasmosis in Hungary. Acute disease was observed in five animals, two of which died. Anaplasma-carrier state was diagnosed in 69 (92%) of cattle. Further evaluation of 24 blood samples revealed concurrent infections with Mycoplasma wenyonii and '. Candidatus M. haemobos' in 22 and 21 animals, respectively. In addition, two cows were identified with rickettsaemia. Regarding molecular investigation of potential hard tick vectors, Haemaphysalis inermis and Dermacentor marginatus males collected from the animals were PCR-negative. However, in one pool (out of 18) of Ixodes ricinus males, and in six pools (out of 18) of D. reticulatus males the msp4 gene of Anaplasma marginale was detected. In the same I. ricinus pool Anaplasma ovis was also identified. All ticks were negative for haemoplasmas. Anaplasma sequences yielded 97-99% homology to sequences deposited in the Genbank. This is the first report of fatal bovine anaplasmosis associated with divergent A. marginale genotypes and concurrent '. Candidatus M. haemobos' infection, as well as of an A. ovis strain in ticks collected from cattle.